The God Question and Its Relationship to Homeopathy - Pitt, Richard (Homœopathic Links, 2013)
The influence of the modern scientific paradigm in our society and in medicine in particular has led to challenges on the position of traditional religion and also on the validity of homeopathy and other holistic forms of healing. This is part of a larger struggle between secular, materialistic philosophies, and religious/spiritual philosophies and homeopathy has found itself, again, stuck in the middle and especially in the U. K. has found itself under much scrutiny and attack. This article explores some of the philosophical and political influences that have led to this situation, ideally clarifying the position of homeopathy and its role in integrating spiritual and scientific ideals.
Keywords: God; Religion; Secularism; Materialism; The Enlightenment; Reason; Fundamentalism; Homeopathy; Holism